Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant activity of different solvent extracts of Gliricidia sepium against third instar larvae of Helicoverpa armigera (Hubner) (Lepidoptera : Noctuidae)

Abstract: Plant based pesticides are known as phytopesticides. Phytopesticide formulations offer a more eco-friendly approach to Insect Pest Management than chemical pesticides. The biological compounds present in these formulations have several biological activities against insect pests. In the present work, an attempt has been made to study the antifeedant activity of Gliricidia sepium leaf extracts using three solvents, i.e; petroleum ether, ethyl acetate and methanol against third instar larvae of Helicoverpa armige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A study has also shown that pawpaw leaf extract exhibited prevented feeding by Spodoptera litura larvae (Rahayu et al, 2020). A group of researchers have demonstrated that terpenoids and phenols present in plant material inhibit larval feeding and can also disrupt hormonal balance or make food unpalatable (Jose and Sujatha, 2017). In some cases, they can also act on the chemosensillar of the larvae resulting in feeding deterrence.…”
Section: Discussionmentioning
confidence: 99%
“…A study has also shown that pawpaw leaf extract exhibited prevented feeding by Spodoptera litura larvae (Rahayu et al, 2020). A group of researchers have demonstrated that terpenoids and phenols present in plant material inhibit larval feeding and can also disrupt hormonal balance or make food unpalatable (Jose and Sujatha, 2017). In some cases, they can also act on the chemosensillar of the larvae resulting in feeding deterrence.…”
Section: Discussionmentioning
confidence: 99%
“…Frazier signified that antifeedants can be found amongst all the major classes of secondary metabolites as they are toxic substances against insects (Frazier, 1986). Various secondary metabolites including alkaloids, chromenes, coumarins, cucurbitacins, phenolics, phenols, polyacetylenes, quassinoids, saponins, tannins, terpenes and terpenoids were reported as potent insect antifeedants (Schoonhoven, 1982;Adeyemi, 2010;Lingathurai et al, 2011;Kumar et al, 2013;Adeyemi and Mohammed, 2014;Jose and Sujatha, 2017). Effective natural antifeedants are triterpenes, sesquiterpene lactones and alkaloids, cucurbitacines, quinines and phenols and the potent antifeedants belong to the terpenoid group, which has the greatest number and diversity of known antifeedants compounds (Nawrot et al, 1986;Norris, 1986;Van beek and Groot, 1986;Adeyemi and Mohammed, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the treatment might have caused a disruption in the hormonal balance that rendered the food unpalatable to the beetles. Several studies indicated that the secondary compounds of plants are toxic to insects and contain elements that are similar to the molting hormones that reduce the productivity of adult insects [12,13]. [14], indicated the superiority of the terpene extract of leaves of Concorpus lancifolius in causing higher mortality rate of adults of the small grain bug Rhyzopertha dominica and the red flour beetles Tribolium castaneum (14.18 and 12.00 %, respectively) at a concentration of 30 mg/ ml.…”
Section: Effects Of Crude Terpenes Extracts From a Majus Leaves And F...mentioning
confidence: 99%